Cerebrospinal fluid metabolomics: detection of neuroinflammation in human central nervous system disease. Issue 8 (6th August 2021) - Yan, Jingya; Kuzhiumparambil, Unnikrishnan; Bandodkar, Sushil; Dale, Russell C; Fu, Shanlin
Abstract: The high morbidity and mortality of neuroinflammatory diseases drives significant interest in understanding the underlying mechanisms involved in the innate and adaptive immune response of the central nervous system (CNS). Diagnostic biomarkers are important to define treatable neuroinflammation. Metabolomics is a rapidly evolving research area offering novel insights into metabolic pathways, and elucidation of reliable metabolites as biomarkers for diseases. This review focuses on the emerging literature regarding the detection of neuroinflammation using cerebrospinal fluid (CSF) metabolomics in human cohort studies. Studies of classic neuroinflammatory disorders such as encephalitis, CNS infection and multiple sclerosis confirm the utility of CSF metabolomics. Additionally, studies in neurodegeneration and neuropsychiatry support the emerging potential of CSF metabolomics to detect neuroinflammation in common CNS diseases such as Alzheimer's disease and depression. We demonstrate metabolites in the tryptophan–kynurenine pathway, nitric oxide pathway, neopterin and major lipid species show moderately consistent ability to differentiate patients with neuroinflammation from controls. Integration of CSF metabolomics into clinical practice is warranted to improve recognition and treatment of neuroinflammation. Abstract : In this review, we summarise the current human evidence of the use of cerebrospinal fluid metabolomics to detect neuroinflammation in acute and chronic neurological and psychiatric diseases. The review highlights the potential utility of metabolites involved in the tryptophan–kynurenine and nitric oxide pathway and neopterin as biomarkers for neuroinflammation.